Ag/TiO2 Nanocomposites for Nanothermometry in the Biological Environment - Roberto Zambon; Marina Franca; Veronica Zani; Roberto Pilot; Silvia Gross; Danilo Pedron; Raffaella Signorini (Engineering Proceedings, 2023)
Local temperature determination is essential to understand heat transport phenomena at the nanoscale and to design nanodevices for biomedical, photonic, and optoelectronic applications. In particular, the detection of the local temperature of the intracellular environment is interesting for photothermal therapy. In the present work, nanoparticles consisting of an Ag core, covered by a TiO2 shell and Ag@TiO2 core–shell, were suitably synthesized through a one-pot method. Silver nanoparticles synthesized in DMF were coated by controlled hydrolysis of titanium tetrabutoxide in the same reaction environment. The synthesis led to nanocomposites where AgNPs were covered by a diffuse layer of anatase. The nanocomposites were characterized using UV/Vis spectroscopy and Raman spectroscopy. The samples obtained proved to be good Raman nanothermometers with a sensitivity comparable to that of simple anatase nanoparticles.